Peran Humas Polsek Dalam Edukasi Keamanan dan Ketertiban Masyarakat di Simpang Kanan, Rokan Hilir Riau - Tiara, Dewi (Universitas Muhammadiyah Sumatera Utara, 2024)
The role of Public Relations is an activity carried out with the aim of maintaining management policies related to developing public opinion or content as well as carrying out its role to shape communication, influence and change knowledge. The purpose of this research is to determine the role of Simpang Kanan Police public relations in educating public security and order. The theory used in this research is the theory of the role of public relations and education. The research methods used are descriptive and observational. This research was conducted on police officers who work at the Simpang Kanan Sector Police (POLSEK) as resource persons. The research results obtained are that there are four roles of public relations used by the Simpang Kanan sector police, namely; Public relations as a communicator uses two methods, namely direct outreach, namely communicating directly with the public and indirect outreach using the mass media. Public relations is a communication technique that is tailored to the target population such as individuals, groups and the masses. Public relations as a facilitator, namely the police, provides more security facilities, such as facilitating security for Christian religious minority residents when worshiping on Sundays. Public relations as an expert advisor, namely the police, has a Friday confide program for the public to freely convey criticism and suggestions so as to create a safe and orderly society.